Vibro-acoustic metamaterial for longitudinal vibration suppression in a low frequency range. (August 2018) - Lee, Su; Ahn, Chang Hoon; Lee, Jin Woo
Highlights: A vibro-acoustic metamaterial proposed for longitudinal vibration suppression. Blocking of longitudinal vibration in an extremely low frequency range. Theoretical approaches developed to predict the stop band of the proposed metamaterial. Explanation of the physical behavior of the metamaterial with negative mass density. Experimental validation of the vibration attenuation of the proposed metamaterial. Abstract: This study proposes a theoretical model of a vibro-acoustic metamaterial for longitudinal vibration suppression in a low frequency range and computationally and experimentally demonstrates the vibration attenuation performance of the proposed metamaterial. The vibro-acoustic coupling analysis is performed on a theoretical model in which a discrete vibration system and a short-length duct are periodically repeated. The transfer matrix method and the Bloch–Floquet theorem were developed to calculate the Bloch phase of a unit cell of the proposed vibro-acoustic metamaterial. Its stop band predicted from the Bloch phase commenced at 0 Hz and coincided with the frequency range of low transmissibility (<1). The effects of unit cell parameters on the upper limit frequency of the stop band are discussed, and the dispersion relation and effective mass density curves of the proposed vibro-acoustic metamaterial explain its underlying physics. The developed theoretical approach is extended to vibro-acoustic metamaterials including a continuous vibration system, instead of a discrete vibration system, for actual application. Finite element analysis and experiments on the extended vibro-acoustic metamaterials were performed to validate the vibration attenuation performance of the proposed metamaterial, which can be used to suppress longitudinal vibration waves transmitted between two mechanical parts. Graphical abstract: Image, graphical abstract